KOMUNIKASI KEBIJAKAN PENYEDIAAN LAJUR SEPEDA DI PROVINSI DKI JAKARTA - Aida Safira; Amni Zarkasyi Rahman; Kismartini Kismartini (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
In the implementation of the provision bike lanes policy in Province DKI Jakarta, there are still many violations of motorized vehicle users crossing bicycle lanes. In fact, according to regulations, motorized vehicles are prohibited from crossing the bicycle lane. This indicates that the policy communication for the provision of bicycle lanes in DKI Jakarta has not been able to influence the behavior of motorized vehicle users to comply with the prohibition on crossing bicycle lanes. This study aims to analyze the policy communication for the provision of bicycle lanes in the DKI Jakarta Province and analyze the driving and inhibiting factors of communication of provision bike lanes policy in Province DKI Jakarta. This research method is descriptive qualitative. Specifically, the researchers made observations on the bicycle lane at RS Fatmawati Raya, Panglima Polim, and Sisingamangaraja Street, South Jakarta Administration City. The result of this research is that the communication of provision bike lanes policy in Province DKI Jakarta is not yet fully good because the transmission is not yet optimal for policy implementers and policy target groups, and the consistency of policy communication is not yet optimal for policy target groups. The driving factor for this policy communication consists of understanding policy implementers related to policies and coordination with various parties to disseminate policy. The inhibiting factors for this policy communication consist of human resources, financial resources, road conditions, traffic conditions, and community behavior. Suggestions from this research are to improve communication of provision bike lanes policy which is still not optimal and reduce barriers to communication of provision bike lanes policy in Province DKI Jakarta.